Evaluasi Manajemen Resiko Teknologi Informasi Menggunakan COBIT 5 dengan Domain EDM03 dan APO12 (Studi Kasus pada UPT-TIK Universitas Brawijaya) - Iqbal Zakkadiaksa; Buce Trias Hanggara; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Brawijaya University Included in the 10 Best Universities in Indonesia, these achievements can not be separated from the implementation of a good service program. One of them is the implementation of information technology services managed by UB's UPT-TIK. The application of IT risk management that has not been optimal in the organization is one of the objectives of this study, namely assessing the application of IT risk management in UPT-TIK Universitas Brawijaya. This assessment and measurement uses the COBIT 5 framework with APO12 and EDM03 domains. This study also analyzes gaps and identifies risks that exist in organizations. The results of this study the UPT-TIK must complete policy documents and standards and implement risk management activities properly. The achievement of organizational risk management capability is at level 0 in the EDM03 and APO12 domains because the results are inseparable due to limited research access. This organizational capability level gap is 1 level each at level 1 in the EDM03 and APO12 domains.